Harnessing optical advantages in computing: a review of current and future trends - Kibebe, Caxton Griffith; Liu, Yue; Tang, Jiaxi (Frontiers in Physics, 2024)
At the intersection of technological evolution and escalating computational demand, the role of optics is reemerging as a transformative force in the field of computing. This article examines the evolving landscape surrounding optical advantages in computing, focusing on current trends and prospects. Optical computing finds applications across various domains, such as parallel processing, high-speed signal processing, energy efficiency, quantum computing, machine learning, secure communication, and signal/image processing. This review synthesizes insights from scholarly articles, peer-reviewed journals, and academic papers to analyze the potential and challenges of leveraging optics for computational tasks. The literature review also critically examines the challenges of adopting optical computing solutions. The recommended multidimensional approach to overcoming adoption challenges involves holistically addressing integration challenges, manufacturing complexities, and infrastructure needs where collaboration will catapult optical computing into an era of computational power. Through a multidimensional exploration, this article provides a comprehensive understanding of the opportunities and challenges in harnessing optical advantages in computing, positioning optical computing as a revolutionary force with far-reaching consequences. Consequently, this review offers insight and guides researchers, industry professionals, and policymakers toward a computational future that maximizes the advantages of optical computing in specific and pivotal application areas, transcending existing boundaries.